Collaborative Governance in an Effort to Reduce Stunting Rate in TTS District, NTT Province - Jacoba Daud Niga (International Journal of Social Service and Research, 2023)
Di Provinsi NTT,, jumlah kasus stunting mencapai 42,62% atau very high prevelance stunting sehingga perlu adanya proses tata kelola kolaborasi (collaborative governance) antar lembaga dalam proses penanganan stunting khususnya di Kabupaten TTS Provinsi NTT sehingga penulis menggunakan model teoritis collaboration processes: inside the black box dari Thomson dan Perry (2006) sebagai suatu kajian teoritis yang mampu menjawab permasalahan tingginya angka prevalensi stunting di Provinsi NTT. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif dengan total jumlah berjumlah 76 orang yang ditetapkan secara purposive kemudian data primer dan data sekunder yang terkumpul dianalisis menggunakan teknik analisis data dari Creswell (2016). Hasil penelitian ditemukan bahwa collaborative governance dalam upaya penurunan angka stunting di Kabupaten TTS Provinsi NTT dianalisis menggunakan pendapat Thomson dan Perry (2006:24-28) dengan hasil temuan sebagai berikut; (1) pada dimensi tata pemerintahan ditemukan bahwa pengambilan keputusan bersama untuk penurunan angka stunting belum dilakukan (2) pada dimensi administrasi masih terbatas pada persoalan integrasi basis data dari tiap-tiap indikator dalam setiap tujuan yang belum lengkap, valid, dan reliabel, (3) pada dimensi otonomi ditemukan bahwa belum ada pemahaman komperhensif mengenai indikator angka stunting oleh pihak-pihak yang berkolaborasi (4) dimensi mutualitas belum efektif karena minimnya saling ketergantungan antar aktor secara kelembagaan serta (5) proses membangun norma sosial ditemukan bahwa belum terdapat kepercayaan dan timbal balik dalam koordinasi penurunan angka stunting di Kabupaten TSS Provinsi NTT. ? ? To: Afrikaans Albanian Amharic Arabic Armenian Assamese Azerbaijani Bangla Bashkir Basque Bosnian Bulgarian Cantonese (Traditional) Catalan Chinese (Literary) Chinese Simplified Chinese Traditional Croatian Czech Danish Dari Divehi Dutch English Estonian Faroese Fijian Filipino Finnish French French (Canada) Galician Ganda Georgian German Greek Gujarati Haitian Creole Hausa Hebrew Hindi Hmong Daw Hungarian Icelandic Igbo Indonesian Inuinnaqtun Inuktitut Inuktitut (Latin) Irish Italian Japanese Kannada Kazakh Khmer Kinyarwanda Konkani Korean Kurdish (Central) Kurdish (Northern) Kyrgyz Lao Latvian Lingala Lithuanian Lower Sorbian Macedonian Maithili Malagasy Malay Malayalam Maltese M?ori Marathi Mongolian (Cyrillic) Mongolian (Traditional) Myanmar (Burmese) Nepali Norwegian Nyanja Odia Pashto Persian Polish Portuguese (Brazil) Portuguese (Portugal) Punjabi Querétaro Otomi Romanian Rundi Russian Samoan Serbian (Cyrillic) Serbian (Latin) Sesotho Sesotho sa Leboa Setswana Shona Sindhi Sinhala Slovak Slovenian Somali Spanish Swahili Swedish Tahitian Tamil Tatar Telugu Thai Tibetan Tigrinya Tongan Turkish Turkmen Ukrainian Upper Sorbian Urdu Uyghur Uzbek (Latin) Vietnamese Welsh Xhosa Yoruba Yucatec Maya Zulu In NTT Province, the number of stunting cases reached 42.62% or very high prevalence of stunting so that there is a need for a collaborative governance process between institutions in the process of handling stunting, especially in TTS District, NTT Province, so the author uses the theoretical model of collaboration processes: inside the black box from Thomson and Perry (2006) as a theoretical study that is able to answer the problem of high stunting prevalence in NTT Province. The method used in this study is a descriptive method with a qualitative approach with a total of 76 people determined purposively then the primary data and secondary data collected were analyzed using data analysis techniques from Creswell (2016). The results of the study found that collaborative governance in an effort to reduce stunting rates in TTS District, NTT Province, was analyzed using the opinions of Thomson and Perry (2006: 24-28) with the following findings; (1) in the governance dimension, it was found that joint decision making to reduce stunting rates had not been carried out, (2) in the administrative dimension it was still limited to the problem of database integration of each indicator in each goal that was not complete, valid, and reliable, (3) in the autonomy dimension, it was found that there was no comprehensive understanding of stunting rate indicators by collaborating parties, (4) the mutuality dimension was not effective due to the lack of mutual dependence between actors institutionally and (5) the process of building social norms found that there has been no trust and reciprocity in coordinating the reduction of stunting rates in TSS District, NTT Province.